Airport redesign for safety and security: Case studies of three Scottish airports - Enoma, Aghahowa; Allen, Stephen; Enoma, Anthony (International Journal of Strategic Property Management, 2009)
This research study set to develop KPIs for airport safety and security using a case study and ethnographic approach to research, the focus was on the role of Facilities Management (FM) in improving safety and security at the airport. The study centred on the management and staff of the case study airport and experts in the field of facilities management and aviation. The methodology for this study is a case study of three Scottish airports, owned and operated by the BAA Scotland (Glasgow, Edinburgh and Aberdeen international airports). Data was collected from Civil Aviation Agency, analysed and presented in the study. The study developed a three ‘AAA’ model (Airport – Aircraft – Airport) and a 3 stage approach to the research process. Evidence in this paper supports the conclusion that planning for airport safety and security are airport specific because no two airports are exactly the same, they differ in their; sizes, mode of operations, passenger type and flight destinations.First Publish Online: 18 Oct 2010